2020
DOI: 10.1111/bjep.12345
|View full text |Cite
|
Sign up to set email alerts
|

The development of an instrument to test pre‐service teachers’ beliefs consistent and inconsistent with self‐regulation theory

Abstract: Background. Students are more effective when they employ appropriate strategies to regulate their learning processes and outcomes. However, many teachers do not provide, or provide very little, explicit instructions to promote this self-regulated learning (SRL). This suggests that teachers' belief systems may include beliefs that may be inconsistent with SRL. Aims. This paper reported the validation of the 78-item Beliefs about Teaching and Learning (BALT) instrument designed to measure pre-service teachers' b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Involvement of all students and rapport between teachers and students might be seen as key characteristics of inclusive learning environments. Moreover, Darmawan et al (2020) relates beliefs about selfregulated learning and constructive teaching. Student teachers with higher constructivist beliefs might also see self-regulated learning as a means of addressing students with disabilities, who are often characterized by self-regulation difficulties (e.g., Korinek and deFur, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of all students and rapport between teachers and students might be seen as key characteristics of inclusive learning environments. Moreover, Darmawan et al (2020) relates beliefs about selfregulated learning and constructive teaching. Student teachers with higher constructivist beliefs might also see self-regulated learning as a means of addressing students with disabilities, who are often characterized by self-regulation difficulties (e.g., Korinek and deFur, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This goes in hand with previous findings (Ebert-May et al, 2011;Assen et al, 2016), even describing a use of transmissive teaching methods despite holding constructivist beliefs about teaching. Moreover, Darmawan et al (2020) highlighted that some student teachers hold constructivist and transmissive beliefs about teaching at the same time. Post-hoc correlational analysis of our data indicated that transmissive and constructivist beliefs were only weakly associated.…”
Section: Discussionmentioning
confidence: 99%
“…This scale was moderately related to the global measure of the intention to implement SRL, indicating that those are related but distinct aspects of SRL implementation. This is of particular relevance because the relationships between teachers' professional competences in SRL and their SRL implementation might vary due to how professional competence and SRL practices of teachers are assessed (Zohar et al, 2001;Darmawan et al, 2020). Further, it has been reported that teachers' self-reports of their promotion of SRL do not necessarily correlate with classroom observations of teachers' SRL instruction (Dignath and Büttner, 2018).…”
Section: Limitation Of Study and Future Outlooksmentioning
confidence: 99%
“…The results of the literature study show that students sometimes answer questions by guessing. Students do not think about answers correctly based on understanding (I. G. N. Darmawan et al, 2020;Moore & Rubbo, 2012;Xiao et al, 2018;S.-N. Zhou et al, 2021).…”
Section: Needs Analysismentioning
confidence: 99%
“…The results of previous research showed that students had difficulty working on the questions. Students in answering questions sometimes make guesses so that students do not think about the answer correctly (I. G. N. Darmawan, Vosniadou, Lawson, Van Deur, & Wyra, 2020;R. Darmawan, 2015;Moore & Rubbo, 2012;Xiao et al, 2018;S.-N. Zhou, Liu, Koenig, Li, & Bao, 2021).…”
Section: Introductionmentioning
confidence: 99%